Alloy design against the solidification cracking in fusion additive manufacturing: an application to a FeCrAl alloy. Issue 8 (3rd August 2021) - Dovgyy, Bogdan; Simonelli, Marco; Pham, Minh-Son
Abstract : This study developed a design methodology against liquid-state cracking by combining the Scheil–Gulliver solidification simulations and Machine Learning analysis to design alloys for Fusion Additive Manufacturing. Applying this design approach resulted in a Fe–20Cr–7Al–4Mo–3Ni. The alloy was successfully printed with relative densities of over 99%. Microstructure of printed material was extensively characterised through scanning and transmission electron microscopy, energy dispersive spectroscopy and x-ray diffraction, confirming a single-phase material with low texture and negligible chemical segregation. Neither solidification nor liquation cracks were detected, supporting the validity of the methodology, however, the alloy suffered from solid-state cracking, hindering the ductility. GRAPHICAL ABSTRACT: IMPACT STATEMENT: A design methodology against solidification and liquation cracking and chemical segregation to assist the alloy design for Additive Manufacturing.